Experimental study on the shear creep behavior of residual soil with varying rock content - Chuang Wang; Jinyu Dong; Shengwen Qi; Jiancang Zhao; Lei Xue; Dengpo Fan (PLoS ONE, 2025)
Using residual soil from the Shanghecun landslide in the western Henan Province, shear creep tests of residual soil samples with different rock contents (RCs) were performed to explore the creep characteristics, creep rate, and long-term strength of the residual soil. The test results indicate that the residual soil samples with different RCs display typical creep characteristics. With increasing RC, both the instantaneous deformation and the total creep deformation of the residual soil gradually decrease. The shear strain of the residual soil increases gradually with increasing shear stress for the different RCs. With increasing time, the slope of the isochronous stress–strain curves of the residual soil samples with different RCs increases gradually. The Burgers model can simulate the rheological process of the residual soil samples with different RCs. The RC has a significant effect on the shear strength and the long-term strength of the residual soil. With increasing RC, the shear strength and the long-term strength of the residual soil gradually increase, with the long-term strength being approximately 39%–63% of the shear strength.